Rancang Bangun Alat Pemantauan Trafik Kendaraan Di Universitas Riau Secara Real Time Menggunakan Lora Protokol - Rio Wira Putra; Yusnita Rahayu (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
This study aims to gather information to count the number of vehicles come to University of Riau in real time and remotely using LoRa protocol, as one of kind data transmission can reach long distance. By counting the number of vehicles that enter every day, the University of Riau can use this data for studying materials in the construction of roads or parking area, that it can provide sufficient facilities in University of Riau.The LoRa protocol is one kind of the Low Power Wide Area Network (LPWAN) access technologies with wide range of characteristics, and easy to activation of devices. In this study, ultrasonic sensor is used to count the number of vehicles that enter daily to University of Riau. Data from ultrasonic measurement is going to sent to laboratorium electro with is approximately 2 kilometers using three point,measurement point, repeater point, and data observation point. Measurements is conducted one workday in the University of Riau environment. The results of this study are obtained that the number of vehicles come to the University of Riau is 1561 unit vehicle in 8 hours, also the reliability of the LoRa protocol used result in number for data transmission, range of transmission distance between 1-2 km, strong signal reception in average -97,47 dB, signal to noise ratio (SNR) as a quality of delivery parameters is 10,63 dB, and the value of the error frequency is -142,82 Hz that exists in data transmission on LoRa. Keywords: LoRa, ultrasonic,vehicles,real time,LPWAN